P300 Neighborhood violent crime and HIV transmission risk: a temporal and spatial exploration of their association. (14th July 2019) - Chandran, Aruna; Wu, Linxuan; Schumacher, Christina; Fields, Errol; Long, Amanda; Jennings, Jacky
Abstract : Background: Experiencing violence, both exposure and victimization, has been associated with negative health outcomes including increased mental health problems and sexual risk behaviors. This ecological analysis aimed to explore the ecologic relationship between aggregate violent crime and HIV transmission risk at the census tract level, including effects of spatial dependence. Methods: Violent crime data reported with address of the incident by the Baltimore Police Department as well as HIV viral load information for those with reported addresses and a viral load of >400 copies/mL collected by the Maryland Department of Health and Mental Hygiene were geocoded and aggregated to the census tract level. Community viral load (CVL) was calculated as the prevalence of uncontrolled viral load in each tract. A negative binomial regression model was used to test the association between violent crime events and CVL, including spatial lag from shared-boundary census tracts as well as mean age, proportion male, labor force participation, educational attainment, and residential instability as key covariates. Results: The annual violent crime rate in Baltimore City in the 5-year period from 2012–2016 was 29.5 per 1, 000 population; rates varied widely between census tracts, ranging from 2 to 189.4 per 1, 000. The mean CVL was 4.27 per 1, 000 population, with a range from 0 to 18.8 by census tract. In the adjusted model, a 100-unit increase in violent crimes was associated with a 19% increase in CVL (RR: 1.19, 95% CI: 1.13, 1.27). Conclusion: Our study shows a statistically significant association between violent crime rates and HIV transmission risk in local areas. This study highlights the need for community-level interventions aimed to address effects of violence exposure in order to effectively combat the ongoing HIV epidemic among vulnerable populations in urban settings. Disclosure: No significant relationships.